Acute eosinophilic pneumonia associated with smoking: a case report - Beenish Fayyaz (Greater Baltimore Medical Center, 2018)
Acute eosinophilic pneumonia (AEP) is commonly misdiagnosed as infectious pneumonia due to presence of fever and radiological features. However, development of peripheral eosinophilia within days of presentation should raise the concern of AEP especially in previously heathy adults with history of recent tobacco smoking.